2008
DOI: 10.1152/ajpheart.00860.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of the left ventricular myocardial interstitium: effects of acute and chronic myocardial edema

Abstract: Myocardial interstitial edema forms as a result of several disease states and clinical interventions. Acute myocardial interstitial edema is associated with compromised systolic and diastolic cardiac function and increased stiffness of the left ventricular chamber. Formation of chronic myocardial interstitial edema results in deposition of interstitial collagen, which causes interstitial fibrosis. To assess the effect of myocardial interstitial edema on the mechanical properties of the left ventricle and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 45 publications
(77 reference statements)
0
70
2
1
Order By: Relevance
“…The elevated LVMI in the AMC group (p = 0.034) results from acute inflammation with successive edema. Edema within the myocardium may result in capillary compression and reduced diastolic and systolic cardiac function [20,21]. We were able to identify wall motion abnormalities in 63 % of the AMC group, which can be broken down into regional distribution in 47 % and global distribution in 16 %.…”
Section: Functional Analysismentioning
confidence: 90%
“…The elevated LVMI in the AMC group (p = 0.034) results from acute inflammation with successive edema. Edema within the myocardium may result in capillary compression and reduced diastolic and systolic cardiac function [20,21]. We were able to identify wall motion abnormalities in 63 % of the AMC group, which can be broken down into regional distribution in 47 % and global distribution in 16 %.…”
Section: Functional Analysismentioning
confidence: 90%
“…In addition, CPB has been associated with decreased myocardial systolic and diastolic function. The prevalence of generalized edema in neonates undergoing cardiovascular surgery with CPB has been reported to be 37% and 54% [4,5,41,42]. In our study, we found that the expression of cGMP and AQP1 were lowest at 6 h, and then began to increase, and reached peak levels at 48 h. Meanwhile, water content of myocardial tissue increased following the CPB surgery, and peaked at 48 h. These findings suggested that cGMP and AQP1 had important roles in water intake during CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the use of cardiopulmonary bypass (CPB) causes profound alterations in the homeostasis of physiological fluids, which often results in myocardial edema. CPB has been associated with decreased myocardial systolic and diastolic function [4,5]. However, none of these aspects of myocardial edema in CPB has been completely characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting alveolar congestion and edema is in part mediated by altered expression of epithelial sodium channel and aquiporin-5 expression. Similar mechanisms may also contribute to myocardial interstitial edema and dysfunction [44]. Transgenic sickle mice subjected to renal IRI exhibited significantly increased myocardial capillary congestion, serum amyloid-P (murine equivalent of C-reaction protein), and renal expression of caspase-3 compared with controls [45].…”
Section: Pathophysiologic Mechanisms Of Aki-induced Cardiac Injurymentioning
confidence: 99%
“…In addition, fluid removal in these patients, either through loop diuretics use [55] or ultrafiltration [56], was associated with higher survival. Fluid accumulation may adversely impact myocardial performance [44], predispose to ventricular arrhythmias [57] and may contribute to maladaptive ventricular remodelling and myocardial fibrosis [44,58].…”
Section: Indirect Mechanismsmentioning
confidence: 99%